Effects of metabolic modifiers on lipogenic and lipolytic gene expressions in sheep - Ab Aziz, Muhamad Faris (2018)
The metabolic modifiers, which include growth hormone, beta-adrenergic agonists, and anabolic steroids, modify animal metabolism and affect the mechanism of nutrient absorption. This experiment aimed to investigate the effect of a beta-adrenergic agonist (BA) and growth hormone (GH) in sheep on processes involved in regulating lipid metabolism, in the tissues principally responsible for nutrient energy metabolism; adipose tissue (subcutaneous adipose tissue), skeletal muscles (longissimus dorsi (LD) and supraspinatus (SS)) and liver. In addition, the study sought to determine whether a transdifferentiated-myogenic cell culture system demonstrating myogenic and adipogenic characteristics would respond to these agents in a similar manner as in vivo.